Synthesis, Spectroscopic, and Antimicrobial Studies on Bivalent Nickel and Copper Complexes of Bis(thiosemicrbazone) - Chandra, Sulekh (Hindawi Publishing Corporation, 2007)
A series of metal complexes of Cu(II) and Ni(II) having the general composition [Formula: see text] with benzil bis(thiosemicarbazone) has been prepared and characterized by element chemical analysis, molar conductance, magnetic susceptibility measurements, and spectral (electronic, IR, EPR, mass) studies. The IR spectral data suggest the involvement of sulphur and azomethane nitrogen in coordination to the central metal ion. On the basis of spectral studies, an octahedral geometry has been assigned for Ni(II) complexes but a tetragonal geometry for Cu(II) complexes. The free ligand and its metal complexes have been tested in vitro against a number of microorganisms in order to assess their antimicrobial properties.